Socio-ecological innovations in the context of the German "Energiewende": An analysis of benefits and necessities in the urban arena - Andrea Wiesholzer (Wuppertal Institut für Klima, Umwelt, Energie, 2018)
Alternative power initiatives are socio-ecological innovations that substantially contribute to city's sustainable development and, therefore, are of particular societal benefit and value. Cities should, consequently, have an inherent interest in their existence and proliferation. This, however, asks for strategic innovation management. While, acknowledgement of the project's innovativeness constitutes the precondition for management, in the further process of steering activity the tasks to reduce hurdles, create open space and support the project's capacities need to be mastered. Thereby, cities are increasingly asked to become innovative themselves in order to find ways to optimally make use of their available tools and capacities. – – Alternative Strom-Initiativen sind sozio-ökologische Innovationen, die wesentlich zur nachhaltigen Entwicklung von Städten beitragen und damit einen besonderen sozialen Nutzen ausüben und Wert haben. Es ist daher im Sinne der Städte selbst deren Existenz und Verbreitung zu fördern. Das bedarf jedoch strategischem Innovationsmanagement. Während die Anerkennung des Innovationspotentials der Alternativprojekte die unabdingbare Voraussetzung für entsprechendes Management darstellt, ist die Aufgabe im weiteren Verlauf des Steuerungshandelns Hürden zu reduzieren, Freiraum zu schaffen und die Kapazitäten und Fähigkeiten der Projekte zu erhöhen. Dabei müssen die Städte zunehmend selbst innovativ werden und Wege finden, ihre verfügbaren Werkzeuge und Rollen optimal einzusetzen.
urn:nbn:de:bsz:wup4-opus-71830
Keywords: 330